Multi-omics reveals the protective mechanisms of Gastrodia elata ethyl acetate extract in vascular dementia - Tao, Jie; Xiao, Tian; Zhang, Zhuo; Cheng, Jianghao; Tan, Jiaoyang; Zhao, Zhourong; Duan, Xiaohua (Frontiers in Pharmacology, 2026)
ObjectiveThis study aimed to investigate the ameliorative effect of the ethyl acetate extract of Gastrodia elata (EEGE) on vascular dementia (VD) and its underlying mechanisms.MethodsA VD rat model was established using the two-vessel occlusion method, while an in vitro cerebral ischemia injury model was constructed by subjecting HT22 cells to oxygen-glucose deprivation. The mechanisms were systematically explored through behavioral tests, ELISA, integrated network analysis, and combined metabolomic and transcriptomic techniques. Key targets were further validated by Western blot.ResultsEEGE significantly improved cognitive function in VD rats. Integrated multi-omics and network analysis predicted that its effects involved two key targets, TNF and IGF1, and identified Parishin A and p-hydroxybenzaldehyde as prioritized drug metabolites for assessment. Subsequent experiments confirmed that EEGE effectively downregulated serum levels of IL-6, TNF-α, and IL-1β by modulating the IGF1-TREM2 signaling axis and the AMPK-SIRT1-FoxO1-NF-κB pathway.ConclusionThe improvement of cognitive dysfunction in vascular dementia by EEGE is closely associated with its regulation of the IGF1-TREM2 axis and the AMPK-SIRT1-FoxO1-NF-κB pathway, thereby mitigating neuroinflammation. This study provides experimental evidence and a potential mechanistic basis for further exploration of EEGE in VD intervention.